2018
DOI: 10.1097/iae.0000000000001777
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Features of Early and Late Age-Related Macular Degeneration

Abstract: Multicolor retinal imaging allowed for improved detection and definition of AMD features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…MCI has been used to image both superficial and deep retinal and choroidal pathologies. [ 12 13 14 15 19 20 ] Muftuoglu et al . have studied epiretinal membrane with MCI and have concluded that it was visualized better on MCI compared to CFP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MCI has been used to image both superficial and deep retinal and choroidal pathologies. [ 12 13 14 15 19 20 ] Muftuoglu et al . have studied epiretinal membrane with MCI and have concluded that it was visualized better on MCI compared to CFP.…”
Section: Discussionmentioning
confidence: 99%
“…have done a comparative analysis of MCI with CFP in age-related macular degeneration and report the sensitivity of 100% to detect atrophy, hypopigmentation, and fibrosis. [ 14 ] MCI aids in differentiation between true and pseudo optic disc edema by showing greenish hue extending well beyond optic disc margin in former. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies that compare FAF to fundus cameras [23][24][25][26], confocal scanning laser ophthalmoscope [23][24][25] (cSLO), and spectral--domain optical coherence tomography [27,28] (sd-OCT) as well as studies comparing multicolour imaging to fundus photography [29], but to our knowledge there has been no study comparing FAF to multicolour imaging.…”
Section: Discussionmentioning
confidence: 99%